Highly Transparent MTO/Ag/MTO Multilayer Film Deposited on Polyethylene Terephthalate Substrate for Transparent Conductive Oxide - Yoon, Sang-Moo; Choi, Ji-Won; Jang, Gun-Eik (AMER SCIENTIFIC PUBLISHERS, 2017)
2.59 wt.% manganese doped tin oxide (MTO)/silver (Ag)/MTO multilayer films were prepared by use of DC/RF magnetron sputtering technique on flexible substrate. The electrical, optical, and structure properties of multilayer films were investigated with varying the thickness of the MTO layer. The optimum thickness of Ag to form a continuous conducting layer was found to be 10 nm. The highest transmittance of multilayer film was about 86.1% at 550 nm wavelength in MTO (40 nm)/Ag (10 nm)/MTO (40 nm). The sheet resistance of multilayer films was almost constant due to the Ag layer, while the resistivity increased simultaneously with increasing thickness of the MTO layer from 20 to 60 nm. The calculated Figure of merit (Phi(TC)) value of multilayer film was 36.6 x 10(-3) Omega(-1). The surface roughness of the optimized films was as low as 0.8 nm.